Risk factors for mental disorder development in asylum seekers and refugees resettled in Western Europe and Turkey: Participant-level analysis of two large prevention studies. (May 2023) - Barbui, Corrado; Tedeschi, Federico; Acarturk, Ceren; Anttila, Minna; Au, Teresa; Baumgartner, Josef; Carswell, Ken; Churchill, Rachel; Cuijpers, Pim; Karyotaki, Eirini; Klein, Thomas; Koesters, Markus; et al.
Background: In asylum seekers and refugees, the frequency of mental disorders, such as depression, anxiety and post-traumatic stress disorder, is higher than the general population, but there is a lack of data on risk factors for the development of mental disorders in this population. Aim: This study investigated the risk factors for mental disorder development in a large group of asylum seekers and refugees resettled in high- and middle-income settings. Methods: Participant-level data from two randomized prevention studies involving asylum seekers and refugees resettled in Western European countries and in Turkey were pooled. The two studies randomized participants with psychological distress, but without a diagnosis of mental disorder, to the Self-Help Plus psychological intervention or enhanced care as usual. At baseline, exposure to potentially traumatic events was measured using the Harvard Trauma Questionnaire-part I, while psychological distress and depressive symptoms were assessed with the General Health Questionnaire and the Patient Health Questionnaire. After 3 and 6 months of follow-up, the proportion of participants who developed a mental disorder was calculated using the Mini International Neuropsychiatric Interview. Results: A total of 1, 101 participants were included in the analysis. At 3- and 6-month follow-up the observed frequency of mental disorders was 13.51% (115/851) and 24.30% (207/852), respectively, while the frequency estimates after missing data imputation were 13.95% and 23.78%, respectively. After controlling for confounders, logistic regression analysis showed that participants with a lower education level ( p = .034), a shorter duration of journey ( p = .057) and arriving from countries with war-related contexts ( p = .017), were more at risk of developing mental disorders. Psychological distress ( p = .004), depression ( p = .001) and exposure to potentially traumatic events ( p = .020) were predictors of mental disorder development. Conclusions: This study identified several risk factors for the development of mental disorders in asylum seekers and refugees, some of which may be the target of risk reduction policies. The identification of asylum seekers and refugees at increased risk of mental disorders should guide the implementation of focused preventative psychological interventions.